2019
DOI: 10.1021/acs.langmuir.9b01429
|View full text |Cite
|
Sign up to set email alerts
|

Probing a Reversible Cationic Switch on a Mixed Self-Assembled Monolayer Using Scanning Electrochemical Microscopy

Abstract: Probing a switch on biomimic membrane surfaces would offer some references to the research on permeability of cytomembranes. In this work, a mixed 11-mercaptoundecanoic acid/1-undecanethiol self-assembled monolayer (MUA/UT SAM) was constructed as a model of a biomembrane. In this mixed SAM, the MUA molecules work as functional parts for the switch and the UT molecules work as diluents. The surface coverage, wetting property, and pK a of this mixed SAM all have been well-inspected. The mixed SAM exhibits excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
(54 reference statements)
0
6
0
1
Order By: Relevance
“…Among them, the degree of the third step was controlled by the surface condition of the substrate. The more negative surface charge was beneficial to the reduction reaction . That is to say, if the SAM substrate could provide more electrons for the Fe­(CN) 6 3– reduction reaction, more Fe­(CN) 6 3– could be reduced to Fe­(CN) 6 4– at the same scan time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the degree of the third step was controlled by the surface condition of the substrate. The more negative surface charge was beneficial to the reduction reaction . That is to say, if the SAM substrate could provide more electrons for the Fe­(CN) 6 3– reduction reaction, more Fe­(CN) 6 3– could be reduced to Fe­(CN) 6 4– at the same scan time.…”
Section: Resultsmentioning
confidence: 99%
“…The more negative surface charge was beneficial to the reduction reaction. 34 That is to say, if the SAM substrate could provide more electrons for the Fe(CN) 6 3− reduction reaction, more Fe(CN) 6 3− could be reduced to Fe(CN) 6 4− at the same scan time. The result would be that more regenerated Fe(CN) 6 4− would be collected by the tip, which would be shown by the increase of the current.…”
Section: Resultsmentioning
confidence: 99%
“…to visualize oxygen consumption (and the respiration activity itself) in living cells, which is an important result, as it indicates cell metabolic vitality. Investigations of cytomembrane permeability can be carried out using biomimetic membrane surfaces, as shown by Huang et al., [134] who used AFM‐SECM to probe the reversible cationic switchable properties of a self‐assembled monolayer and showed that the homogeneous monolayer features a uniform distribution of switch molecules (11‐mercaptoundecanoic acid). The above approach was also used to probe the incorporation of a channel‐forming protein (C2IIa) and the transport of a metal complex through these cationic‐sensitive channels [135] …”
Section: Biospectroelectrochemistry Through Membranes and Cellsmentioning
confidence: 99%
“…图 9 探针向不同基底的渐近曲线图. 黑线: 金基底, 含二茂 铁甲醇的电解液; 红线: 绝缘基底, 含二茂铁甲醇的电解液; 蓝线: MPA SAM修饰的金基底, 含二茂铁甲醇的电解液; 绿 线: MPA SAM修饰的金基底, 含亚铁氰化钾的电解液; 电解 液pH均为6.4 [34] (网络版彩图) [34] (网络版彩图) 图 11 SECM的SG/TC模式中MPA SAM表面氢键向静电转 变过程的示意图 [37] (网络版彩图) 图 13 SECM反馈模式探究SAM表面阳离子开关示意图 [38] (网络版彩图) [39] (网络版彩图) 图 15 基于电荷翻转的天冬氨酸和精氨酸分子识别原理示意图 [39] (网络版彩图) [39] (网络版彩图)…”
Section: Sam表面分子间氢键的定量研究unclassified
“…Figure13 Schematic representation of the investigation of cation switch on SAM surface by feedback of SECM[38] (color online).…”
mentioning
confidence: 99%